Peran fear of missing out (FOMO) dan penggunaan media sosial terhadap artikulasi identitas keislaman pada kalangan milennial muslim yang mengikuti tren hijrah di Instagram - Sabiqotul Husna (Fakultas Psikologi Universitas Indonesia dan Ikatan Psikologi Sosial-HIMPSI, 2023)
Based on study of 177 millennial Muslims in Indonesia who actively engaged in the hijrah movement through their Instagram, this study aims to reveal the relationship between FOMO and problematic use of social media, with the articulation of Islamic identity. The measuring instruments used in this research were the adaptation of the FOMO scale, the adÂaptation of social media disorder scale and the articulation of Islamic identity on Instagram scale. The results of the analysis using multiple regression showed that simultaneously FOMO and problematic use of social media predicted the articulation of Islamic identity with a simultaneous effective contribution of 40.6% (36.7% the contribution of social media use & 3.9% the contribution of FOMO). We also found that FOMO independently had no correlation with the articulation of Islamic identity, but the use of problematic social media proved to have a significant correlation with the articulation of Islamic identity. These findings may serve as a basis for further research related to the theme of religious identity articulation in social media and the formulation of interventions for excessive use of social media.